BIM no ensino: ganhos e impasses - Rudner Fabiano Lopes (2022)
BIM (Building Information Modeling) adoption by the country has grown, given the gains in productivity, reduction of errors and rework in project processes - among other gains perceived by Brazilian civil construction project companies. Although research on the introduction of the BIM methodology in the national construction industry is already emerging, it is necessary to deepen the studies related to the changes caused by BIM in the programs of the Architecture and Urbanism. The research is based on the hypothesis that the projects teaching and learning processes are affected by the introduction of the BIM methodology at the university and that the discussions on this topic should be expanded in order to enhance the positive results and minimize the losts when it is adopted. The methodology adopted consists of a broad bibliographic review and semi-structured interviews with professors and entrepreneurs from the project area. Based on these two instruments, twenty subjects are raised for discussion including the contemplation of the gains and impasses brought to the academy caused by the introduction of BIM methodology and other advanced parameterization digital technologies related to it. The research concludes, after presenting the twenty discussions on the subject, that the absorption by the academy of the BIM methodology is imminent but needs to be carried out with caution and criticism based on the challenges and paradoxes raised by the investigation. It also concludes that there is a need to review the emphasis given in the contents taught in national Architecture and Urbanism courses. Despite this, the presence of BIM in the production of projects does not cause major transformations in creative cognitive thinking and does not clash with the national education guidelines established by the Ministry of Education (MEC) - not configuring a curricular revolution.